Efficacy and safety of tabalumab, an anti-BAFF monoclonal antibody, in patients with moderate-to-severe rheumatoid arthritis and inadequate response to TNF inhibitors: results of a randomised, double-blind, placebo-controlled, phase 3 study. Issue 1 (12th August 2015) - Schiff, Michael; Combe, Bernard; Dörner, Thomas; Kremer, Joel M; Huizinga, Thomas W; Veenhuizen, Melissa; Gill, Anne; Komocsar, Wendy; Berclaz, Pierre-Yves; Ortmann, Robert; Lee, Chin
Abstract : Background: Tabalumab is a human monoclonal antibody that neutralises B-cell activating factor. Objectives: To evaluate tabalumab efficacy and safety in patients with rheumatoid arthritis (RA). Methods: This phase 3, randomised, double-blind, placebo-controlled study evaluated 456 patients with active RA after 24-week treatment with subcutaneous tabalumab (120 mg every 4 weeks (120/Q4W) or 90 mg every 2 weeks (90/Q2W)) versus placebo, with loading doses (240 or 180 mg) at week 0. Patients were allowed background disease-modifying antirheumatic drugs and previously discontinued ≥1 tumour necrosis factor α inhibitors for lack of efficacy/intolerance. Primary end point was American College of Rheumatology 20% (ACR20) response at 24 weeks. This study was terminated early due to futility. Results: Most patients had moderate-to-high baseline disease activity. There was no significant difference in week 24 ACR20 responses between 120/Q4W, 90/Q2W, and placebo (17.6%, 24.3%, 20%) per non-responder imputation analysis. Mean percent changes in CD20+ B-cell count (−10.8%, −9.6%, +10.9%) demonstrated expected pharmacodynamic effects. Treatment-emergent adverse events (AEs) were similar (59.5%, 51.7%, 52.6%), as were AE discontinuations (2.6%, 2.7%, 2.6%), serious AEs (4.6%, 4.1%, 3.9%), serious infectious events (1.3%, 0, 0) and events of interest: infections (23.5%, 25.9%, 24%), injection site reactions (13.1%, 25.8%, 11%) and allergy/hypersensitivity (3.9%, 4.1%, 3.9%) reports. Incidence of treatment-emergent antidrug antibodies was similar to placebo (3.9%, 4.8%, 3.9%). No deaths or new/unexpected safety findings were reported. Conclusions: Tabalumab did not demonstrate clinical efficacy in patients with RA in this phase 3 study, despite evidence of biological activity. There were no notable differences in safety parameters between tabalumab treatment groups and placebo. Trial registration number: NCT01202773.